OPTIMIZATION OF GEDONG GINCU MANGO DISTRIBUTION COSTS IN MAJALENGKA DISTRICT - Sulaksana, Jaka; Marina, Ida; Fatimah, Inka (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Facing free trade, Indonesia is required to increase the performance of mango production in order to compete with mangoes from other countries, but the performance of gedong gincu mango agribusiness still faces a number of obstacles, both on farm and off farm. One of them is to optimize distribution costs by designing a transportation model to determine the amount of goods that must be sent from each source to each destination in such a way that the total transportation cost is minimum. The transportation model used is Vogel's Approximation Method. The purpose of this research was to find out the description of the distribution of gedong gincu mangoes in Majalengka District, the distribution costs incurred from source to destination and find out the optimization of distribution costs. The method used was quantitative with survey research techniques. The results of this research were an overview of the distribution of Gedong Gincu mangoes involving 5 parties, namely farmers, collectors, dealers, retailers and consumers which can be done with 4 marketing channels. The distribution costs incurred were different, on the four channels the lowest distribution costs are Rp 29,000 and the highest fee is Rp 74,000/kg. In channel I, it did not carry out cost optimization calculations because it did not make shipments out of town, for optimization in channel II it is Rp 13,950,000, channel III is Rp 249,100,000 and channel IV is Rp 250,980,000. Thus, it can be concluded that the lowest cost is on ordinary channel II. Further research is recommended to perform optimal testing by means of a stepping stone.